Dinamika Ukuran Perusahaan dan Rasio Keuangan dalam Mengontrol Agresivitas Pajak - Asiah, Neng; Sabaruddinsah; Ayu, Sekar (Jurnal Akuntansi Bisnis Pelita Bangsa, 2024)
This study aims to determine the effect of profitability, liquidity, leverage and company size on tax aggressiveness, defined as a company's willingness to exploit the tax code to its advantage. The research employs a quantitative methodology, utilising secondary data in the form of annual financial reports. The population is comprised of food and beverage sector industrial companies listed on the Indonesia Stock Exchange for the period spanning 2020-2022. The research methodology employed in this study is descriptive quantitative, utilising descriptive statistical data analysis, classical assumption testing, panel data regression, MRA testing, hypothesis testing and determination coefficient testing. The results demonstrated that there is no significant correlation between profitability and tax aggressiveness. Conversely, a positive and statistically significant correlation was observed between leverage and tax aggressiveness. The moderating effect of company size on the relationship between profitability, leverage and tax aggressiveness cannot be established.